Volume 4: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27102
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Investigation of the Effect of Cooling Channel Crossflow on Film Cooling Performance

Abstract: This paper presents an experimental and numerical investigation into film cooling performance over a flat plate. As previous studies have shown, the flow situation at the entry-side of the cooling hole shows a notable effect on film cooling performance. The present investigation takes this into account feeding the cooling holes from an internal cooling channel and not from a stagnant plenum. High resolution heat transfer coefficient and adiabatic film cooling effectiveness distributions received from transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This study focuses on the influence of the rib orientation in the internal cooling passage on the external cooling characteristics along the blade outer surface. Kissel et al (10) experimented the difference of cooling performance between the smooth case and the ribbed case for internal passage. They also carried out numerical analyses to show that the ribbed case enlarged the separation bubble at the hole inlet and resulted in the change of flow conditions at the hole outlet.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the influence of the rib orientation in the internal cooling passage on the external cooling characteristics along the blade outer surface. Kissel et al (10) experimented the difference of cooling performance between the smooth case and the ribbed case for internal passage. They also carried out numerical analyses to show that the ribbed case enlarged the separation bubble at the hole inlet and resulted in the change of flow conditions at the hole outlet.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are reports on the effects of the density ratio (1) , the blowing angle (2) , and the geometry of injection holes (3) (4) for the film cooling while there are reports on the effects of geometry of turbulence promoters (5) (6) , the passage bend (7) , and the blade rotation (8) for the internal convection cooling. In contrast, studies on the combined effects of the film cooling and the internal convection cooling are rather scarce except for a few studies such as those of Gritsch et al (9) , Fawcett et al (10) Kissel et al (11) , and Sakai et al (12) . The authors showed that the film cooling characteristics are different between the case where the cooling air is supplied from the internal flow and the case where it is supplied from a stagnant plenum.…”
Section: Introductionmentioning
confidence: 91%
“…Their study also showed that internal crossflow improved the performance of cylindrical holes, but reduced the performance of shaped holes. Kissel et al [13] varied the coolant channel Re and found the heat transfer coefficient decreasing with increasing Re, while the adiabatic effectiveness is nearly unaffected. Saumweber and Schulz [14] studied internal crossflow oriented perpendicular to the mainstream and found, as [10] did, a single helical motion in the hole.…”
Section: Previous Work On Film Coolingmentioning
confidence: 99%
“…To date, no studies have looked at the consequence of internal crossflow on compound-angle film cooling holes. Also, there has been little effort to validate the CFD, the notable exception being [13], but they do not match the experimental data. The effect of turbulence model choice on film cooling, especially for complex geometries is not well understood.…”
Section: Objectivementioning
confidence: 99%